CLINICAL AND HISTOPATHOLOGICAL AXILLARY ASSESSMENT - Navarro, Diana Taissa Sampaio Marinho; Aguiar, Manuela Gomes de; Galvão, Marcos Felipe de Oliveira; Germano, Thaís Cristina Oliveira; Lajus, Tirzah Braz Petta; Oliveira, Teresa Cristina Andrade de (Mastology, 2018)
Introduction: The proper selection of patients for sentinel lymph node biopsy is essential and depends on the evaluation of the patient’s prediction for lymph node involvement and an evaluation of the accuracy of the clinical examination. Objective: This study aimed to evaluate the axillary contents of 102 breast cancer patients with tumors between 3 and 5 centimeters who underwent axillary dissection between January 2010 and December 2013. Methods: The data were categorized according to positive or negative axillary clinical evaluation and positive or negative anatomopathological evaluation. Results: The value for positive predictive values for physical examination was 83.5% and the negative predictive value was 34.88%. In addition, axillary physical examination showed 63.6% sensitivity and 60% specificity. Most patients with axillary involvement in the anatomopathological evaluation correlated with tumor grade, size, location and angiolymphatic invasion. Conclusion: It is believed that a better evaluation of the prediction of lymph node involvement, considering some clinicopathological risk factors in patients with suspicious lymph nodes, should be performed to aid the preoperative study of the axilla and the axillary approach screening.